MAF-7 loaded silver nano composite material as well as preparation method and application thereof

By preparing MAF-7-loaded silver nanocomposites, the problem of excessively fast silver ions release in the prior art was solved, and the slow release and efficient antibacterial effect in neutral and acidic environments were achieved, which was particularly suitable for the treatment of root canal infection.

CN119386203APending Publication Date: 2025-02-07TIANJIN DENTAL HOSPITAL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411517462.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing metal-organic framework nanomaterials loaded with silver ions cannot achieve slow release of silver ions, resulting in excessively rapid release of silver ions, high aggregation, increased toxicity and reduced effective concentration, especially in acidic environments.

Method used

By preparing MAF-7-loaded silver nanocomposite, Zn2+ salt is used to react with triazole and ammonia to form MAF-7, and react with Ag+ salt in a suitable solvent to achieve slow release of silver ions.

Benefits of technology

It achieves good antibacterial effects on Enterococcus faecalis in neutral and acidic environments, especially under acidic conditions, and has great potential to be used as an antibacterial agent in the treatment of root canal infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386203A_ABST
    Figure CN119386203A_ABST
Patent Text Reader

Abstract

The invention provides an MAF-7 silver-loaded nano composite material as well as a preparation method and application thereof, the preparation method comprises the following steps: S1, dissolving Zn < 2 + > salt and triazole in a first solvent, and then adding ammonia water for reaction to obtain MAF-7; s2, MAF-7 and Ag < + > salt are dissolved in a second solvent for a reaction, and the MAF-7 loaded silver nano composite material is obtained. The MAF-7 loaded silver nano composite material is prepared through a simple synthesis method, slow release of Ag < + > can be achieved, and the MAF-7 loaded silver nano composite material has a good antibacterial effect on enterococcus faecalis in neutral (pH 7.4) and acidic (pH 4.7) environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial materials, and particularly relates to a MAF-7 loaded silver nanocomposite material, a preparation method and application thereof. Background Art

[0002] Pulpitis and apical periodontitis are common oral diseases, the main cause of which is bacterial infection. Studies have shown that Enterococcus faecalis is one of the dominant bacteria in infected root canals, especially in retreated root canals. The detection rate of Enterococcus faecalis is particularly high in retreated root canals. Enterococcus faecalis is a facultative anaerobic Gram-positive bacterium that is acid-resistant and can survive and reproduce in infected root canals. The main reason for the persistence of apical periodontitis is the presence of Enterococcus faecalis, as this bacterium can tolerate commonly used root canal disinfectants.

[0003] Silver ion (Ag + ) has a certain antibacterial effect on Enterococcus faecalis, which can destroy the integrity of the cell membrane, destroy the cell wall structure, and limit the biological activity of bacterial nucleic acids and proteins. These effects ultimately lead to cell death or inhibit the growth and reproduction of bacteria. Generally speaking, silver ions have better bactericidal effects in neutral or weakly alkaline environments, while in acidic environments, due to their instability and aggregation, the bactericidal effect is poor. In addition, the efficacy of pure silver ions in root canal treatment is essentially limited.

[0004] Metal-organic frameworks (MOFs) are a class of porous materials composed of metal ions and organic ligands. They have various functionalities, such as high drug encapsulation efficiency, responsive drug release, and low cytotoxicity. Therefore, MOFs have potential applications in drug delivery. In recent years, the application of MOFs in antibacterial effects has received much attention. The metal ions released by MOFs can damage the integrity of cell membranes and trigger the generation of free radicals through redox processes. These free radicals subsequently damage the structure of cell membranes and DNA, ultimately leading to cell death. The released organic ligands can also interact with bacterial cell membranes, destroying their structure and causing cell death. In addition, MOFs have a highly controllable pore structure that can adsorb bacterial metabolites and nutrients, thereby inhibiting bacterial growth and reproduction.

[0005] Ag is loaded on MOF materials, and its antibacterial properties can be significantly improved compared to single Ag ions or MOF materials. The Chinese patent literature with publication number CN115772272B discloses a silver-modified two-dimensional metal-organic framework nanomaterial and its preparation method and application in the preparation of antibacterial products. Ag is loaded on Zr-Fc-MOF nanosheets by xenon lamp illumination in-situ reduction method to synthesize Zr-Fc-MOF@Ag material, and the photothermal properties of the antibacterial material can accelerate the release of silver ions to achieve efficient antibacterial effect. Compared with traditional single materials and single sterilization methods, photothermal acceleration of silver ion release can achieve a huge improvement in antibacterial effect. However, the existing metal organic framework nanomaterials loaded with silver ions cannot achieve slow release of silver ions. The excessive release of silver ions makes it easy to aggregate, which can lead to excessive toxicity on the one hand and reduce its effective concentration on the other hand. The antibacterial activity is not enough under neutral or acidic conditions, especially in acidic environments where Enterococcus faecalis is relatively tolerant. Summary of the invention

[0006] The technical problem solved by the present invention is to provide a MAF-7 loaded silver nanocomposite material, a preparation method and application thereof. The MAF-7 loaded silver nanocomposite material is prepared by a simple synthesis method, which can realize the silver + It has a slow release and has a good antibacterial effect against Enterococcus faecalis in neutral (pH 7.4) and acidic (pH 4.7) environments.

[0007] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a MAF-7 loaded silver nanocomposite material, comprising the following steps:

[0008] S1. Zn 2+ The salt and triazole are dissolved in a first solvent, and then aqueous ammonia is added to react to obtain MAF-7;

[0009] S2. Combine MAF-7 with Ag + The salt is dissolved in the second solvent and reacted to obtain the MAF-7 loaded silver nanocomposite material.

[0010] Preferably, Zn 2+ The molar ratio of triazole to triazole is 1:7.2-8.4.

[0011] Preferably, Zn 2+ The molar ratio of ammonia to ammonia water is 1:2.6-3.2.

[0012] Preferably, MAF-7 and Ag + The molar ratio is 1:0.5~2.

[0013] Preferably, the Zn 2+ Salt is Zn2+ One or a mixture of nitrates, hydrochlorides, sulfates;

[0014] The Ag + Salt is Ag + One or a mixture of nitrates and sulfates;

[0015] The first solvent is water;

[0016] The second solvent is methanol.

[0017] Preferably, step S1 specifically comprises the following steps: Zn 2+ The salt and triazole are dissolved in a first solvent to prepare a solution, and then ammonia water is added and stirred to react for 10 minutes to 1 hour to obtain a first mixture. The first mixture is centrifuged to remove the supernatant, and then washed and dried to obtain MAF-7.

[0018] Preferably, step S2 specifically comprises the following steps: + The salt is dissolved in the second solvent to prepare a solution, and then MAF-7 is added and stirred for reaction for 10 minutes to 1 hour to obtain a second mixture. The second mixture is centrifuged to remove the supernatant, and then washed and dried to obtain the MAF-7 loaded silver nanocomposite material.

[0019] The second aspect of the present invention provides a MAF-7 loaded silver nanocomposite material prepared by the above preparation method.

[0020] The third aspect of the present invention provides a use of the above MAF-7 loaded silver nanocomposite material in the preparation of antibacterial materials or bactericidal materials.

[0021] Preferably, under a neutral environment, the MAF-7 loaded silver nanocomposite material is used at a concentration of ≥400 μg / mL;

[0022] In an acidic environment, the use concentration of the MAF-7 loaded silver nanocomposite material is ≥600 μg / mL.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention prepares MAF-7 loaded silver nanocomposite material by a simple synthesis method. Wherein, metal oxazolidinone framework-7 (MAF-7) is a MOF material composed of zinc ions and 3-methyl-1H-1,2,4-triazole ligands, and MAF-7 itself has certain antibacterial properties by releasing zinc ions, and the silver ions loaded thereon also have good antibacterial properties. Moreover, MAF-7, as a carrier for loading silver ions, can regulate the release rate of silver ions, so that silver ions are slowly released, avoiding the problem of aggregation due to the large-scale release of silver ions, which reduces the antibacterial properties. In addition, compared with other MOF materials, the 1-N atoms of MAF-7 are not bound, so the ligand is more likely to be an active site for guest binding.

[0025] The present invention successfully synthesized MAF-7 loaded silver nanocomposite material, and used a variety of characterization techniques to conduct in-depth analysis of its structure and properties; the antibacterial activity of MAF-7 loaded silver nanocomposite material against Enterococcus faecalis was systematically studied. The results showed that the synthesized MAF-7 loaded silver nanocomposite material had a significant inhibitory effect on the growth of Enterococcus faecalis, especially under acidic conditions. Under acidic conditions, the bactericidal effect of MAF-7 loaded silver nanocomposite material was significantly better than that of silver nitrate (AgNO3). This indicates that MAF-7 loaded silver nanocomposite material has great potential as an antibacterial agent for the treatment of the main bacteria in root canal infection. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The powder X-ray diffraction (PXRD) patterns of MAF-7 and MAF-7 loaded silver nanocomposite prepared in Example 1 of the present invention;

[0027] Figure 2 1 is the infrared spectra of MAF-7 and MAF-7 loaded silver nanocomposite prepared in Example 1 of the present invention;

[0028] Figure 3 1 is the Raman spectra of MAF-7 and MAF-7 loaded silver nanocomposite prepared in Example 1 of the present invention;

[0029] Figure 4 The transmission electron microscope (TEM) and scanning electron microscope (SEM) images of MAF-7 and MAF-7 loaded silver nanocomposite prepared in Example 1 of the present invention are shown in FIG. + / MAF-7 indicates MAF-7 loaded with silver nanocomposite;

[0030] Figure 5 It is the element mapping of C, N, Zn and Ag of the MAF-7 loaded silver nanocomposite prepared in Example 1 of the present invention;

[0031] Figure 6This is the EDS spectrum analysis of the MAF-7 loaded silver nanocomposite material prepared in Example 1 of the present invention;

[0032] Figure 7 It is a graph of the metal ion release of MAF-7 loaded silver nanocomposite material calculated based on the detection results of inductively coupled plasma mass spectrometry (ICP-AES) technology;

[0033] Figure 8 (a) is a photograph of the minimum inhibitory concentration (MIC) of the MAF-7 loaded silver nanocomposite material, after different concentrations of the MAF-7 loaded silver nanocomposite material were mixed with Enterococcus faecalis and cultured at 37°C for 24 hours; (b) is a photograph of the bacterial colonies formed after different concentrations of the MAF-7 loaded silver nanocomposite material were mixed with Enterococcus faecalis under neutral conditions (pH=7.4) when the minimum bactericidal concentration (MBC) of the MAF-7 loaded silver nanocomposite material was determined; (c) is a photograph of the bacterial colonies formed after different concentrations of the MAF-7 loaded silver nanocomposite material were mixed with Enterococcus faecalis under acidic conditions (pH=4.7) when the minimum bactericidal concentration (MBC) of the MAF-7 loaded silver nanocomposite material was determined; (d) is a bacterial growth curve under the action of different concentrations of the MAF-7 loaded silver nanocomposite material under neutral conditions; (e) is a bacterial growth curve under the action of different concentrations of the MAF-7 loaded silver nanocomposite material under acidic conditions;

[0034] Fig. 9 (a) shows the bactericidal effect of positive control and silver nitrate (AgNO3) on Enterococcus faecalis under neutral conditions (pH = 7.4); (b) shows the bactericidal effect of negative control and MAF-7 loaded silver nanocomposite on Enterococcus faecalis under neutral conditions (pH = 7.4); (c) shows the bactericidal effect of positive control and silver nitrate (AgNO3) on Enterococcus faecalis under acidic conditions (pH = 4.7); (d) shows the bactericidal effect of negative control and MAF-7 loaded silver nanocomposite on Enterococcus faecalis under acidic conditions (pH = 4.7);

[0035] Fig.10 The figure shows the bactericidal effect of MAF-7 loaded silver nanocomposites under neutral and acidic conditions. (a) is a photo of bacterial colonies formed by Enterococcus faecalis after mixing different concentrations of MAF-7 loaded silver nanocomposites under neutral conditions; (b) is a fluorescent image of live bacteria / dead bacteria staining experiment after mixing different concentrations of MAF-7 loaded silver nanocomposites under neutral conditions; (c) is a photo of bacterial colonies formed by Enterococcus faecalis after mixing different concentrations of MAF-7 loaded silver nanocomposites under acidic conditions; (d) is a fluorescent image of live bacteria / dead bacteria staining experiment after mixing different concentrations of MAF-7 loaded silver nanocomposites under acidic conditions. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] A first aspect of an embodiment of the present invention provides a method for preparing a MAF-7 loaded silver nanocomposite material, comprising the following steps:

[0038] S1. Zn 2+ The salt and triazole are dissolved in a first solvent, and then aqueous ammonia is added to react to obtain MAF-7;

[0039] S2. Combine MAF-7 with Ag + The salt is dissolved in the second solvent and reacted to obtain the MAF-7 loaded silver nanocomposite material.

[0040] The present invention prepares MAF-7 loaded silver nanocomposite material by a simple synthesis method. Wherein, metal oxazolidinone framework-7 (MAF-7) is a MOF material composed of zinc ions and 3-methyl-1H-1,2,4-triazole ligands, and MAF-7 itself has certain antibacterial properties by releasing zinc ions. And the silver ions loaded thereon also have certain antibacterial properties. Moreover, MAF-7, as a carrier for loading silver ions, can regulate the release rate of silver ions, so that silver ions are slowly released, avoiding the problem of aggregation due to the large-scale release of silver ions, which reduces the antibacterial properties. In addition, compared with other MOF materials, the 1-N atoms of MAF-7 are not bound, so the ligand is more likely to be an active site for guest binding.

[0041] In some embodiments, Zn 2+ The molar ratio of Zn to triazole affects the conversion rate and yield of MAF-7. Experimental studies have found that, preferably, Zn 2+ The molar ratio of Zn to triazole is 1:7.2-8.4. Within this ratio range, the yield of MAF-7 is higher. Further preferably, Zn 2+ The molar ratio of triazole to triazole is 1:8.

[0042] In some embodiments, ammonia is used as Zn 2+ The catalyst for the reaction with triazole, the amount of ammonia added affects the yield of MAF-7. Experimental studies have found that preferably, Zn 2+ The molar ratio of Zn to ammonia in aqueous ammonia is 1:2.6-3.2. Within this ratio range, the yield of MAF-7 is higher.2+ The molar ratio of ammonia to ammonia water is 1:3.

[0043] In some embodiments, MAF-7 and Ag + The influence of the molar ratio of Ag on MAF-7 + The actual loading amount of Ag under acidic and neutral conditions + The release amount and release rate of Ag + The release rate is too fast, which will lead to a large amount of Ag + Aggregation, Ag + Aggregation will cause a significant reduction in the antibacterial effect; on the other hand, in MAF-7 loaded silver nanocomposites, Ag + Has higher bactericidal activity, Zn 2+ It has higher antibacterial activity. The two have different antibacterial mechanisms and different antibacterial effects under different conditions. + The loading amount affects the Ag + With Zn 2+ Therefore, the release ratio of MAF-7 and Ag + The molar ratio of MAF-7 to Ag has a significant effect on the antibacterial properties of the nanocomposite. + The molar ratio of MAF-7 to Ag is 1:0.5 to 2. Within this ratio range, the antibacterial property of the MAF-7 loaded silver nanocomposite material is better. + The molar ratio of MAF-7 to Ag is 1:0.67 to 1.5. + The molar ratio is 1:1.

[0044] In some embodiments, the Zn 2+ Salt is Zn 2+ Preferably, Zn 2+ Salt is Zn 2+ of nitrates.

[0045] In some embodiments, the Ag + Salt is Ag + Preferably, Ag + Salt is Ag + of nitrates.

[0046] In some embodiments, the first solvent may be water, methanol, ethanol or the like. Preferably, the first solvent is water.

[0047] In some embodiments, the second solvent may be water, methanol, ethanol or the like. Preferably, the second solvent is methanol.

[0048] In some embodiments, step S1 specifically comprises the following steps: 2+ The salt and triazole are dissolved in a first solvent to prepare a solution, and then ammonia water is added and stirred to react for 10 minutes to 1 hour to obtain a first mixture. The first mixture is centrifuged to remove the supernatant, and then washed and dried to obtain MAF-7.

[0049] In some embodiments, step S2 specifically comprises the following steps: + The salt is dissolved in the second solvent to prepare a solution, and then MAF-7 is added and stirred for reaction for 10 minutes to 1 hour to obtain a second mixture. The second mixture is centrifuged to remove the supernatant, and then washed and dried to obtain the MAF-7 loaded silver nanocomposite material.

[0050] A second aspect of the embodiments of the present invention provides a MAF-7 loaded silver nanocomposite material prepared by the above-mentioned preparation method.

[0051] A third aspect of the embodiments of the present invention provides a use of the above-mentioned MAF-7 loaded silver nanocomposite material in the preparation of antibacterial materials or bactericidal materials.

[0052] Preferably, under a neutral environment, the MAF-7 loaded silver nanocomposite material is used at a concentration of ≥400 μg / mL;

[0053] In an acidic environment, the use concentration of the MAF-7 loaded silver nanocomposite material is ≥600 μg / mL.

[0054] Experimental methods

[0055] Characterization of MAF-7 loaded silver nanocomposites

[0056] An appropriate amount of MAF-7 loaded silver nanocomposite and MAF-7 dry powder were placed on a sample stand. The crystal forms of MAF-7 loaded silver nanocomposite and MAF-7 were determined by powder X-ray diffraction (PXRD). The scanning angle was 3°-50°, the speed was 8° / min, and λ=1.540593.

[0057] MAF-7 loaded silver nanocomposite powder was dispersed in ethanol and dropped onto a silicon wafer. After vacuum drying, the morphology of MAF-7 loaded silver nanocomposite was observed by high-resolution field emission electron microscopy. A certain amount of dried MAF-7 loaded silver nanocomposite powder was collected and placed on a conductive adhesive, and the elemental composition of MAF-7 loaded silver nanocomposite was determined by energy dispersive spectroscopy (EDS).

[0058] Ag + and Zn 2+ Release

[0059] First, 10 mg of MAF-7 loaded silver nanocomposite powder was dispersed in 10 mL of phosphate buffer (PBS, pH 7.4). The plate was shaken on a vortex shaker for 5 minutes and then placed in a 37 ° C incubator. 5 mL of supernatant was sampled each time, and then 5 mL of fresh buffer was added and cultured. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) was used to measure the Ag released in the sample solution on days 1, 3, 6, 9, 12 and 15. + and Zn 2+ Then, calculate the Ag at different time points + and Zn 2+ The cumulative release amount and release rate.

[0060] Resurgence of Enterococcus faecalis

[0061] Enterococcus faecalis was inoculated on BHI agar plates by streaking and cultured in a 37°C, saturated CO2 incubator for 24 hours. Monoclonal colonies on the plates were selected and inoculated into 2 mL of BHI liquid medium and cultured for 24 hours. BHI solution was used as a negative control.

[0062] Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC)

[0063] The MIC of MAF-7 loaded silver nanocomposites under different pH conditions was determined by microdilution method. 8 CFU / mL of Enterococcus faecalis suspension in BHI liquid medium. Antimicrobial solutions were prepared using double-diluted MAF-7 loaded silver nanocomposites at concentrations of 800 μg / mL, 400 μg / mL, 200 μg / mL, 100 μg / mL, 50 μg / mL, 25 μg / mL, 12.5 μg / mL, 6.25 μg / mL, and 3.125 μg / mL. Then, 100 μL of these antimicrobial solutions were inoculated into each well of a 96-well plate, using three wells for each concentration. 5 μL of a concentration of 1×10 8 CFU / mL of Enterococcus faecalis, and mixed well, and cultured at 37°C for 24 hours. 8 CFU / mL of Enterococcus faecalis was used as a positive control. The lowest MAF-7 loaded silver nanocomposite concentration that did not cause visible turbidity was considered the MIC.

[0064] The MBC of MAF-7 loaded silver nanocomposites under different pH conditions was measured using the plate coating method. Then, 100 μL of the mixed suspension was evenly coated on an agar plate. After culturing at 37 °C for 24 h, photos were taken to identify the bacterial colonies on each plate and to determine the MBC that killed 99.9% of the bacteria at the lowest MAF-7 loaded silver nanocomposite concentration.

[0065] For comparison, MAF-7 loaded silver nanocomposites with desired concentrations were tested in parallel under neutral (pH 7.4) and acidic (pH 4.7) conditions.

[0066] Bacterial growth curves of MAF-7 loaded with silver nanocomposites at different concentrations

[0067] Enterococcus faecalis (E.faecalis) was cultured in brain heart infusion (BHI) medium at 37°C for 24 h. In addition, 4 mL of MAF-7 loaded silver nanocomposite solutions with different concentrations were prepared, with final concentrations of 800 μg / mL, 600 μg / mL, 400 μg / mL, 200 μg / mL, 100 μg / mL, 50 μg / mL and 25 μg / mL. Then, 80 μL of 1×10 8 CFU / mL bacterial suspension. BHI liquid medium containing Enterococcus faecalis was used as a positive control. The mixture was incubated at 37°C and the growth rate of Enterococcus faecalis was monitored at 600nm in a time-dependent manner using a spectrophotometer.

[0068] For comparison, MAF-7 loaded silver nanocomposites with desired concentrations were tested in parallel under neutral (pH 7.4) and acidic (pH 4.7) conditions.

[0069] Bactericidal effect of different concentrations of MAF-7 loaded with silver nanocomposites

[0070] The survival rate of bacteria after treatment with MAF-7 loaded silver nanocomposites was detected by the coating plate method. The bacterial suspension containing different concentrations of MAF-7 loaded silver nanocomposites was incubated in an oscillator for 30 minutes, and BHI was used as a blank control. After incubation, 100 μL of the mixed suspension was evenly coated on an agar plate and cultured at 37 ° C for 24 hours. Photos were taken to identify the bacterial colonies growing on each plate.

[0071] Then, the bactericidal activity of MAF-7 loaded silver nanocomposites against Enterococcus faecalis was evaluated by live / dead bacterial staining. According to the instructions of the LIVE / DEAD BacLightTM Bacterial Viability Kit, 1.5 mL of each incubated bacterial suspension was centrifuged at 15000 rpm for 15 minutes and the supernatant was removed. Then, 0.5 mL of 0.85% saline was added to the bacteria for resuspending. Equal amounts of components A and B were evenly mixed in a microcentrifuge tube. 1.5 μL of the dye mixture was thoroughly mixed with 0.5 mL of the bacterial suspension and incubated at room temperature in the dark for 15 minutes. 5 μL of the bacterial suspension containing the dye was placed on a glass slide and an 18 mm 2 The live / dead bacteria were observed under a fluorescence microscope.

[0072] Example 1 Preparation and characterization of MAF-7 loaded silver nanocomposite

[0073] The preparation method of the MAF-7 loaded silver nanocomposite material of the present embodiment comprises the following steps:

[0074] S1. Zn(NO3)·6H2O (148.75 mg, 0.5 mol) and C3H5N3 (332.4 mg, 4 mol) were mixed in 10 mL of deionized water to prepare a solution. Then, 100 μL of ammonia water (25%) was added and stirred for reaction for 1 hour. Subsequently, the mixture was centrifuged at 8000 rpm for 10 minutes and the supernatant was removed. The product was washed with deionized water and finally dried under vacuum to obtain MAF-7.

[0075] S2. Dissolve AgNO3 in methanol to prepare a 26 mM solution, then add MAF-7 (60 mg) and mix. + The molar ratio of silver nanoparticles to MAF-7 was 1:1, and the mixture was stirred for 1 hour. The mixture was centrifuged at 8000 rpm for 10 minutes, the supernatant was removed, and the precipitate was washed with methanol and dried under vacuum to obtain a MAF-7 loaded silver nanocomposite material.

[0076] The characterization results of the product obtained in this example are as follows:

[0077] Figure 1The powder X-ray diffraction (PXRD) patterns of MAF-7 and MAF-7 loaded silver nanocomposites are shown. The characteristic diffraction peaks of MAF-7 and MAF-7 loaded silver nanocomposites are in good agreement with the simulation results. The experimentally synthesized MAF-7 and MAF-7 loaded silver nanocomposites have peaks at 7.4°(110), 10.4°(200) and 12.7°(211), which are highly consistent with the simulated peaks of MAF-7. Therefore, it can be inferred that the crystal structure of the prepared MAF-7 loaded silver nanocomposites is consistent with that of MAF-7, and the adsorption of silver ions does not lead to a significant change in the phase purity of MAF-7.

[0078] Figure 2 The infrared spectra of MAF-7 and MAF-7 loaded with silver nanocomposites are shown. The analysis shows that the framework structure of MAF-7 remains basically unchanged after loading silver ions. It is worth noting that at 826 cm -1 The additional peak observed at 500 cm indicates the interaction between silver ions and the MAF-7 framework. The appearance of this characteristic peak proves that silver ions have been successfully incorporated into the MAF-7 structure, thus confirming the effective loading of silver ions. Raman spectroscopy shows that after the incorporation of silver ions, the peak at about 500 cm -1 Several nearby peaks merged into a broad single peak. This phenomenon may be attributed to the interaction between silver ions and organic ligands or metal centers within MOF, resulting in changes in local vibration modes. This indicates that silver ions have been successfully integrated into the MOF framework ( Figure 3 ).

[0079] The microstructures of MAF-7 and MAF-7 loaded silver nanocomposites were investigated using transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Figure 4 As shown. It can be observed that MAF-7 is composed of spherical particles formed by the aggregation of a large number of nanoparticles. After loading silver ions, the size and morphology of the nanoparticles did not change significantly. These images show that the prepared MAF-7 and MAF-7 loaded silver nanocomposites formed aggregated nanoparticles. The elemental composition of MAF-7 loaded silver nanocomposites was analyzed using SEM-EDS. Figure 5 The elemental mapping of C, N, Zn, and Ag is shown, and a concentrated distribution of Ag in the sample is observed, indicating that Ag decomposition occurs in the prepared material. + In addition, EDS spectroscopy analysis of MAF-7 loaded silver nanocomposites was also performed ( Figure 6 ), the signals of C, N, Zn and Ag were detected, verifying the successful preparation of MAF-7 loaded silver nanocomposite materials.

[0080] The concentration of trace metal ions was detected by inductively coupled plasma mass spectrometry (ICP-AES), and the release amount and release rate of metal ions were calculated based on this. Figure 7 It shows that, over time, Ag + and Zn 2+ The release of Zn increased, but to different degrees. The structure of MAF-7 is relatively stable. 2+ The release of Ag was low, only 19.8% after 15 days. + The release rate slowed down, gradually reaching 78.9% after 15 days, which is expected to reduce the possibility of aggregation and potential excessive toxicity.

[0081] In addition, the Ag content in 10 mg MAF-7 loaded silver nanocomposites was detected by ICP-AES technology. + The content is 2.3 mg, accounting for 23% of the mass fraction.

[0082] Example 2 Antibacterial and antibacterial properties of MAF-7 loaded silver nanocomposite materials

[0083] An antimicrobial substance is considered bactericidal if it kills bacteria and bacteriostatic if it inhibits bacterial growth.First, the antibacterial activity of MAF-7-loaded silver nanocomposites against Enterococcus faecalis was evaluated by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of MAF-7-loaded silver nanocomposites in neutral (pH 7.4) and acidic (pH 4.7) environments.

[0084] The results showed that MAF-7 loaded silver nanocomposites exhibited excellent antibacterial properties in both neutral and acidic environments. Under neutral conditions, the MIC of MAF-7 loaded silver nanocomposites was 200 μg / mL, while under acidic conditions, the MIC was 100 μg / mL (e.g. Figure 8 (a)). Therefore, MAF-7 loaded silver nanocomposites exhibited better antibacterial activity under acidic conditions. In addition, MAF-7 itself may release more organic ligands in an acidic environment, and its pore structure can adsorb bacterial metabolites and nutrients. Therefore, it can be inferred that MAF-7 loaded silver nanocomposites also have a good antibacterial effect on infected root canals in an acidic environment.

[0085] However, the MBC of MAF-7 loaded silver nanocomposites against Enterococcus faecalis showed opposite results under different conditions. Figure 8Figures (b)-(c) show that under neutral conditions, the MBC of MAF-7 loaded silver nanocomposites is 400 μg / mL, while under acidic conditions, the MBC is 800 μg / mL. Although MAF-7 loaded silver nanocomposites exhibit significant antibacterial activity in acidic environments, their bactericidal ability is slightly weaker. Analysis shows that this may be due to the fact that silver ions tend to aggregate in acidic environments, resulting in a decrease in their effective concentration. Studies have shown that although Zn 2+ It has strong antibacterial activity, but its bactericidal activity is weaker than that of Ag. + This may be due to slight differences in their main antimicrobial mechanisms. + The antibacterial mechanisms of Zn include: first, interaction with the bacterial cell envelope; second, interaction with intracellular molecules; and third, generation of reactive oxygen species (ROS). 2+ The antibacterial mechanism of Zn mainly involves binding to bacterial cell membranes, interfering with bacterial metabolism, and thus inhibiting bacterial growth and reproduction. 2+ The significant increase of + The decrease in effective concentration leads to a decrease in its bactericidal activity.

[0086] According to the growth curve of Enterococcus faecalis under different concentrations of MAF-7 loaded silver nanocomposites, under neutral conditions (pH 7.4), when the concentration of MAF-7 loaded silver nanocomposites was greater than or equal to the minimum inhibitory concentration (MIC, 200 μg / mL), it showed good antibacterial effect and completely inhibited the growth of Enterococcus faecalis after 24 hours. MAF-7 loaded silver nanocomposites with a concentration lower than MIC had a certain antibacterial effect compared with the positive control within 12 hours, but the bacterial growth was obvious after 12 hours (such as Figure 8 as shown in (d) above.

[0087] Under acidic conditions (pH 4.7), when the concentration of MAF-7 loaded silver nanocomposite was greater than or equal to MIC (100 μg / mL), it also showed good antibacterial effect and completely inhibited the growth of Enterococcus faecalis after 24 hours. MAF-7 loaded silver nanocomposite with a concentration lower than MIC also had a certain antibacterial effect compared with the positive control within 12 hours, but the bacterial growth was obvious after 12 hours (such as Figure 8 as shown in (e)).

[0088] The above results further indicate that MAF-7 loaded silver nanocomposite has good and stable antibacterial effect, especially in acidic environment.

[0089] Example 3 Comparison of bactericidal effects of silver nitrate and MAF-7 loaded silver nanocomposites

[0090] Silver ions in silver nitrate (AgNO3) and MAF-7 loaded silver nanocomposites with equal concentrations were mixed with bacterial suspensions, and the mixtures were evenly coated on plates and incubated for 24 hours. Under neutral conditions, it was found that AgNO3 and MAF-7 loaded silver nanocomposites with equal silver ion concentrations had comparable bactericidal effects ( Fig. 9 However, under acidic conditions, MAF-7 loaded silver nanocomposites showed better bactericidal effect than AgNO3 with the same silver ion concentration ( Fig. 9 Specifically, at a concentration of 800 μg / mL, the sample treated with AgNO3 still showed some bacterial colonies, while no colonies were observed in the sample treated with MAF-7 loaded silver nanocomposite. The enhanced bactericidal effect of MAF-7 loaded silver nanocomposite under acidic conditions can be attributed to the Ag + Partial encapsulation within the MOF framework resulted in incomplete release under neutral conditions. In contrast, the acidic environment induced the degradation of the MAF-7 framework, leading to the release of silver and zinc ions, which have a synergistic bactericidal effect. These findings suggest that the synthesized MAF-7 loaded silver nanocomposites exhibit superior bactericidal properties under acidic conditions compared to AgNO3.

[0091] Example 4 Bactericidal effect of MAF-7 loaded silver nanocomposite materials at different concentrations

[0092] Different concentrations of MAF-7 loaded silver nanocomposites were mixed with bacterial suspensions, and the mixtures were evenly spread on plates, followed by 24-hour incubation. Under neutral conditions (pH 7.4), no bacterial colonies were observed when the concentration of MAF-7 loaded silver nanocomposites was ≥400 μg / mL. In contrast, at concentrations below 400 μg / mL, different numbers of colonies (e.g. Fig.10 Under acidic conditions (pH 4.7), no colonies were detected when the concentration of MAF-7 loaded silver nanocomposites was ≥600 μg / mL, while at concentrations below 600 μg / mL, different numbers of colonies were observed (as shown in Fig.10(c)-(d)). Specifically, at concentrations of 50 μg / mL, 100 μg / mL, and 200 μg / mL, the number of colonies under acidic conditions was lower than that under neutral conditions, indicating that the bactericidal effect was enhanced in an acidic environment. However, at a concentration of 400 μg / mL, the number of colonies under acidic conditions was slightly greater than that under neutral conditions. This observation is consistent with the result that the minimum bactericidal concentration (MBC) under acidic conditions is higher than that under neutral conditions. The analysis showed that at higher concentrations, silver ions tend to aggregate in an acidic environment, which reduces the bactericidal effect of high-concentration silver ions under acidic conditions. In contrast, the bactericidal effect under neutral conditions is better.

[0093] Example 5

[0094] The MAF-7 loaded silver nanocomposite material of this embodiment is different from that of embodiment 1 in that in the preparation method, MAF-7 and Ag + The molar ratio of MAF-7 to Ag is different. + The molar ratio is 2:1, and the remaining steps are the same as in Example 1.

[0095] Example 6

[0096] The MAF-7 loaded silver nanocomposite material of this embodiment is different from that of embodiment 1 in that in the preparation method, MAF-7 and Ag + The molar ratio of MAF-7 to Ag is different. + The molar ratio of is 1.5:1, and the remaining steps are the same as in Example 1.

[0097] Example 7

[0098] The MAF-7 loaded silver nanocomposite material of this embodiment is different from that of embodiment 1 in that in the preparation method, MAF-7 and Ag + The molar ratio of MAF-7 to Ag is different. + The molar ratio of is 1:1.5, and the remaining steps are the same as in Example 1.

[0099] Example 8

[0100] The MAF-7 loaded silver nanocomposite material of this embodiment is different from that of embodiment 1 in that in the preparation method, MAF-7 and Ag + The molar ratio of MAF-7 to Ag is different. + The molar ratio of is 1:2, and the remaining steps are the same as in Example 1.

[0101] The antibacterial properties of the MAF-7 loaded silver nanocomposites prepared in the above Examples 1, 5-8 were tested. The antibacterial activity of the MAF-7 loaded silver nanocomposites against Enterococcus faecalis was evaluated by measuring the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the MAF-7 loaded silver nanocomposites in neutral (pH 7.4) and acidic (pH 4.7) environments. The smaller the MIC and MBC, the higher the antibacterial activity. As shown in Table 1 below.

[0102] MAF-7 loaded silver nanocomposites can release Ag under both acidic and neutral conditions + and Zn 2+ , while Ag + and Zn 2+ The antibacterial mechanisms of Ag + Has good bactericidal properties, Zn 2+ It has a certain antibacterial effect, but its bactericidal property is lower than Ag. + weak.

[0103] Under acidic conditions, Ag + It is easy to aggregate, which reduces its bactericidal activity; while MAF-7 releases Zn under acidic conditions 2+ , the decomposition of organic framework increases, and the antibacterial property is enhanced. In a neutral environment, the Ag released mainly + Play an antibacterial role, Ag + :MAF-7 ratio increased, Ag + The content is relatively increased, and the antibacterial and bactericidal properties are enhanced; in an acidic environment, Ag + 、Zn 2+ Ag and decomposed organic framework can play an antibacterial role. + :MAF-7 ratio increased, Ag + The aggregation phenomenon is obvious, and the antibacterial and bactericidal properties are weakened.

[0104] From the data in the table below, we can see that MAF-7 and Ag + The overall antibacterial properties of the materials are different due to the different molar ratios. Among them, the antibacterial properties of Examples 1, 6, and 7 are better than those of Examples 5 and 8, and are preferred embodiments, while Example 1 is the most preferred embodiment.

[0105] Table 1

[0106]

[0107] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a MAF-7 loaded silver nanocomposite material, characterized in that: The following steps are involved: S1. Zn 2+ The salt and triazole are dissolved in a first solvent, and then aqueous ammonia is added to react to obtain MAF-7; S2. Combine MAF-7 with Ag + The salt is dissolved in the second solvent and reacted to obtain the MAF-7 loaded silver nanocomposite material.

2. The preparation method according to claim 1, characterized in that: Zn 2+ The molar ratio of triazole to triazole is 1:7.2-8.

4.

3. The preparation method according to claim 1, characterized in that: Zn 2+ The molar ratio of ammonia to ammonia water is 1:2.6-3.

2.

4. The preparation method according to claim 1, characterized in that: MAF-7 and Ag + The molar ratio is 1:0.5~2.

5. The preparation method according to claim 1, characterized in that: The Zn 2+ Salt is Zn 2+ One or a mixture of nitrates, hydrochlorides, sulfates; The Ag + Salt is Ag + One or a mixture of nitrates and sulfates; The first solvent is water; The second solvent is methanol.

6. The preparation method according to claim 1, characterized in that: Step S1 specifically includes the following steps: Zn 2+ The salt and triazole are dissolved in a first solvent to prepare a solution, and then ammonia water is added and stirred to react for 10 minutes to 1 hour to obtain a first mixture. The first mixture is centrifuged to remove the supernatant, and then washed and dried to obtain MAF-7.

7. The preparation method according to claim 1, characterized in that: Step S2 specifically includes the following steps: + The salt is dissolved in the second solvent to prepare a solution, and then MAF-7 is added and stirred for reaction for 10 minutes to 1 hour to obtain a second mixture. The second mixture is centrifuged to remove the supernatant, and then washed and dried to obtain the MAF-7 loaded silver nanocomposite material.

8. A MAF-7 loaded silver nanocomposite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the MAF-7 loaded silver nanocomposite material as claimed in claim 8 in the preparation of antibacterial or bactericidal materials.

10. The use according to claim 9, characterized in that: Under a neutral environment, the MAF-7 loaded silver nanocomposite material is used at a concentration of ≥400 μg / mL; In an acidic environment, the use concentration of the MAF-7 loaded silver nanocomposite material is ≥600 μg / mL.

Citation Information

Patent Citations

  • A silver-modified two-dimensional metal-organic framework nanomaterial, its preparation method, and its application in the preparation of antibacterial products.

    CN115772272B